Between ‘Land Grabs’ and Agricultural Investment: Land Rent Contracts with Foreign Investors and Ethiopia’s Normative Setting in Focus - Stebek, EN (Mizan law review, 2012)
This article examines whether the land rent contracts and the Ethiopian legal framework on rural land use rights can assure win-win mutual benefits expected from large-scale land transfers to foreign investors. The article further examines the challenges in the realization of the Seven Principles for Responsible Agricultural Investments prepared by FAO, IFAD, UNCTAD and the World Bank Group as a framework of standards for the current global dialogue on large-scale farmland acquisitions.  I argue that land-use insecurity in the Ethiopian context results from the extensive powers of executive offices that are empowered to dispossess holders and reallocate land to investors. These powers can be even more discretionary where land transfers are made without prior mapping and demarcation of protected forests and wildlife, and where registration and the issuance of land-holding certificates to smallholder farmers and pastoralists have not yet been made. The article suggests the need to rectify the gaps in the land transfer contracts and most importantly, the need to render the government a custodian (and not owner) of land in conformity with the FDRE Constitution and to ensure that the termination of land use rights is decided by courts so that executive offices would not perform the dual functions of revoking and reallocating rural land use rights.  Key words: Land grabs, responsible agricultural investment, land rights, farmland acquisition, Ethiopia